Municipal storm water management - Debo, Thomas N. (Thomas Neil), 1941-; Reese, Andrew J. (CRC Press [Imprint] Abingdon : Taylor & Francis Group Florence : Taylor & Francis Group [Distributor], 2002)
Annotation Designed to be a stand alone desktop reference for the Stormwater manager, designer, and planner, the bestselling Municipal Stormwater Management has been expanded and updated. Here is what's new in the second edition: New material on complying with the NPDES program for Phase II and in running a stormwater quality programThe latest information on stormwater utilitiesMetric versions of many of the equations, charts, and design monographs The latest information on Best Management Practices (BMPs)New concepts in stormwater master planningAn understanding of the recent evolution in stormwater practiceSite design practices to reduce stormwater impactsLots of additional information related to the development of municipal stormwater programsThe authors provide the most up-to-date information available, including water quality best management practices and stormwater master and quality management plans. They present little known but valuable tables, charts, and procedures covering both common designs and more specialized situations. Both English and Metric versions of charts and nomographs are included where available and where deemed useful for the designer.The text presents an understanding of what works and what doesn't in real-world municipalities. Topics on planning and institutional concerns focus on programs dealing with public awareness, ordinances and regulations, and financing. Technical design topics range from the practical aspects of hydrologic procedures to the design of culverts and storm drainage systems. This stand-alone document provides all the essential information for the design and analysis of most stormwater management facilities.Municipal Stormwater Management, Second Editioncovers all aspects of municipal Stormwater management, from planning and institutional concerns to technical design considerations. It details the design applications and the institutional aspects of Stormwater management that planners and administrators face on a daily basis. The material and depth of coverage make this book the perfect text for both professional and academic use.
Scholarly & Professional